2008
DOI: 10.1007/s12010-008-8428-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Exopolysaccharides in Liquid Suspension Culture of Nostoc flagelliforme Cells

Abstract: The liquid suspension culture of dissociated Nostoc flagelliforme cells was investigated. It was found that the growth rate of N. flagelliforme cells and the accumulation of exopolysaccharides (EPS) increased prominently when NaNO(3) and KH(2)PO(4) were added in the liquid BG-11culture medium though phosphate had little effect on EPS yield for specific mass of cells. N. flagelliforme cells grew well at 25 degrees C and neutral pH, however, a lower or higher temperature and weak alkaline can promote EPS accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…Many species of cyanobacteria, including N. flagelliforme , show a combined nitrogen-dependent rapid growth and EPS synthesis in liquid culture conditions (Otero and Vincenzini, 2003; Pereira et al, 2009; Yu et al, 2010). However, the trichomes or micro-colonies of N. flagelliforme could be induced to exhibit relatively straight elongation in nitrogen-free BG11 0 solution (Rippka et al, 1979), as described in the Materials and Methods (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of cyanobacteria, including N. flagelliforme , show a combined nitrogen-dependent rapid growth and EPS synthesis in liquid culture conditions (Otero and Vincenzini, 2003; Pereira et al, 2009; Yu et al, 2010). However, the trichomes or micro-colonies of N. flagelliforme could be induced to exhibit relatively straight elongation in nitrogen-free BG11 0 solution (Rippka et al, 1979), as described in the Materials and Methods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relative proportion of strip-like N. flagelliforme is also found to increase on relatively humid slopes or shaded lands. Liquid-cultured N. flagelliforme has been developed and serves as a valuable source for producing EPS (Gao and Ye, 2003; Su et al, 2008; Yu et al, 2010; Han et al, 2014a). In a long-term induction (1–3 months) by low ultraviolet (UV)-B radiation and/or periodic desiccation, single trichomes from the liquid culture could develop into colonial filaments 1–3 cm long on solid media (Feng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This type of linear growth is not unknown for cyanobacteria, particularly for strains that produce large amounts of structured extracellular polysaccharides, and may be related to the considerable amount of energy spent in the production of EPS and the physical constraints caused by these extracellular complex structures (Yu et al, 2009(Yu et al, , 2010. The higher tolerance exhibited by Gloeothece wild-type and mutant for Pb 2+ strongly indicates that these organisms are more severely affected by Cu 2+ than by Pb 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies on the influence of light intensity (Friedman et al, 1991;Moreno et al, 1998;Otero and Vincenzini, 2003;Trabelsi et al, 2009;Yu et al, 2010;Mota et al, 2013) and wavelengths (Ehling-Schulz et al, 1997;Chen et al, 2009) on EPS yield have been reported. Different light regimens (continuous light and light-dark cycles) do not significantly affect the monosaccharidic composition of EPS (Vincenzini et al, 1993;De Philippis and Vincenzini, 1998).…”
mentioning
confidence: 99%
“…1). (Friedman et al, 1991;Moreno et al, 1998;Otero and Vincenzini, 2003;Trabelsi et al, 2009;Yu et al, 2010;Mota et al, 2013), suggesting that energy availability significantly affects the EPS biosynthesis of cyanobacteria. Higher light intensity results in higher EPS production, which may constitute mechanism of releasing the excess energy absorbed by the cells (Mota et al, 2013) and increasing CO2 fixation rate in the cells under high light intensity.…”
mentioning
confidence: 99%